PROSEDUR PEMERIKSAAN RADIOGRAFI HIP JOINT POST-OPERASI TOTAL HIP ARTHOPLASTY - Wildan Hanayzul Fahmi; Panji Wibowo Nurcahyo (Perhimpunan Radiografer Indonesia (PARI), 2022)
ABSTRACT Background: Conventional radiographic examination of the hip joint post-operative Total Hip Arthoplasty aims to propose a prosthesis on the Hip Joint. Parameters assessed with AP Pelvis Projection include leg length, center of horizontal rotation, center of vertical rotation. Acetabular inclination, femoral stem positioning, and cement mentle thickness can be assessed on AP Unilateral Hip Projection and AP Pelvis Projection, whereas Acetabular anteversion can only be seen with inferosuperior axiolateral projections. Conventional radiographic examination of the hip joint after Total Hip Arthoplasty surgery at the Radiology Installation of Tidar Magelang Hospital was only carried out by AP Pelvis Projection. Method: This research type is qualitative with case study approach. Data collection methods consisted triangulation method of observation, interview and documentation. Research subject consist 3 radiology technologist, 1 specialist doctor, and 1 radiology doctor. Collected data will be analyzed with interactive technique transformed into transcript and then reducted. After that the data will be shown as quotation. Based on data and literature study, author will conclude. Result: Radiographic exam of hip joint post-operation Total Hip Arthoplasty in Radiology Departement of RSUD Tidar Magelang is done in accordance to standard procedure of only using AP Pelvic projection. This is done to acquire radiographic image of both sides of the hip joints, the whole prosthetic component, and reducing the radiation received. Central point set on the center of symphisis pubic, with area of collimation as wide as the detector to acquire image of the whole prosthetic. Without lateral projection the lateral view of the prosthetic cannot be acquired causing the absence of the radiographic images of both acetabular anteversion and the acetabular retroversion. Causing the angle of acetabular component of the prosthetic cannot be measured. Resulting in the loss additional information. Conclusion: AP Pelvic projection is in accordance to standard procedure of Radiology Departement of RSUD Tidar Magelang, specialist doctor’s request, and had shown the radiographic image of the whole prosthetic component. From author’s opinion, it is best that lateral projection still be done to acquire complete information of the radiographic evaluation of post-operation Total Hip Arthoplasty.